The Effect of NPL, BOPO, NIM on ROA of State-Owned Banks Listed on The Indonesia Stock Exchange - Akbar, Agung Ali; Nurdiansyah, Dian Hakip (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This study aims to find out about the effect of NPL, BOPO, NIM against ROA of BUMN banks listed on the Indonesian stock exchange, using Verification descriptive research method with a quantitative approach. The dependent variable used in this study is Return On Assets (Y). The independent variables used in this study are NPL (X1), BOPO (X2), and NIM (X3). The population in this study are state-owned banks listed on the Indonesia Stock Exchange, totaling 4 banks. In this study, sample deception was carried out by means of non-probability sampling with saturated sampling, where samples of all members of the population were used as samples. Based on the research, several conclusions can be drawn, namely: Net Interest Margin (NIM) on Return on Assets (ROA), but there is no effect of Operating Expenses and operating income (BOPO) on Return on Assets (ROA), while simultaneously there is an influence of NPL, NIM and BOPO on Return on Assets (ROA).